A highly dispersed multi-component co-doped carbon nanobelt and its preparation method and application

By using a Fenton-like oxidation method to prepare an iron-modified partially oxidized polyaniline precursor in an acidic environment and performing high-temperature carbonization, highly dispersed multi-component co-doped carbon nanoribbons were prepared, which solved the problem of low catalytic activity of existing carbon nanomaterials. solve the problem, achieve efficient degradation of organic pollutants, and have good recycling performance.

CN118239475BActive Publication Date: 2025-01-21WUHAN TEXTILE UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410356717.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-01-21
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

When existing carbon nanomaterials catalytically activate persulfate, there are problems such as low catalytic activity, easy deactivation, and the reaction effect is greatly affected by environmental variables.

Method used

Highly dispersed multi-component co-doped carbon nanoribbons were used to prepare iron-modified partially oxidized polyaniline precursors in an acidic environment through a Fenton-like oxidation method, and were carbonized at high temperatures in an inert atmosphere to achieve in-situ co-doping.

Benefits of technology

It improves the catalytic performance of carbon nanomaterials, can efficiently activate monopersulfate and selectively generate singlet oxygen, significantly improves the degradation effect of organic pollutants, and has good recycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118239475B_ABST
    Figure CN118239475B_ABST
Patent Text Reader

Abstract

The present invention discloses a highly dispersed multi-component co-doped carbon nanobelt and a preparation method and application thereof. The preparation method comprises: preparing an iron-modified partially oxidized polyaniline precursor by a Fenton-like oxidation method, and then directly converting the precursor into a highly dispersed iron, nitrogen, oxygen and other multi-component co-doped carbon nanobelt through high-temperature carbonization. A single precursor is used in the carbonization process, and no external carbon source and other doping raw materials are required, nor is a subsequent pickling step required, so that highly dispersed iron, nitrogen, oxygen and other multi-component in-situ co-doped carbon nanobelts can be prepared in one step. The method is simple in process and easy to control and scale up production. The obtained material has a one-dimensional ribbon-shaped graphite phase microstructure and multi-level pores, contains at least several co-doped elements such as highly dispersed iron, nitrogen, oxygen, etc., is rich in defect sites, is non-toxic and harmless, and can be used to activate monopersulfate to selectively generate singlet oxygen, and efficiently degrade organic pollutants in complex water bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nanocatalytic materials and water treatment, and in particular to a highly dispersed multi-component co-doped carbon nanobelt for activating monopersulfate, and a preparation method and application thereof. Background Art

[0002] Organic matter (such as organic dyes and drug molecules) is a common type of pollutant in water bodies. Advanced oxidation technology based on persulfate (PS) can effectively treat organic wastewater. Transition metal (TM) catalysts are commonly used to activate persulfate, but TM catalysis not only has problems such as high cost and secondary pollution caused by metal loss, but also usually produces free radicals (such as SO4 ·- , OH, O2 ·- ) pathway to oxidatively degrade organic pollutants, and the degradation effect is significantly affected by the anions and natural organic matter coexisting in the actual water body.

[0003] Carbon materials (such as graphene and carbon nanotubes) can activate PS and avoid secondary pollution caused by metal loss. However, single or pure phase carbon materials have a stable conjugated system and have problems such as poor electron transmission ability and insufficient electron donation ability, resulting in low catalytic activity and easy deactivation. In addition, free radicals and non-free radicals (such as singlet oxygen and surface activated complexes) active species usually coexist in the reaction system, and the degradation effect is greatly affected by environmental variables.

[0004] Doping with non-metallic or metal atoms can disrupt the stable conjugated system of perfect carbon materials, adjust the electronic structure of carbon atoms, and improve their conductivity, hydrophilicity, and electron transport capacity, thereby enhancing the catalytic performance of carbon materials. However, existing preparation methods often involve special raw materials and complex processes, making them difficult to promote and scale up. For example, Chinese patent CN116550285A discloses a method for preparing nitrogen-doped carbon materials that can be used to adsorb CO2 and VOCs. This method uses a mixture of a carbon material precursor and a nitrogen source as raw material. The nitrogen-doped carbon material is prepared through pre-oxidation, carbonization activation, acid washing, water washing, and drying. Chinese patent CN111744523B discloses a method for preparing nitrogen-doped carbon materials for tetracycline degradation. The precursor used for pyrolysis is a mixture of a petroleum-based material rich in aromatic components and nitrogen-containing small molecules (such as cyanamide, melamine, and urea). The pyrolysis process includes secondary high-temperature carbonization (carbonization temperatures are 500-600°C and 700-1000°C, respectively). Chinese patent CN117138815A discloses a method for preparing an iron-nitrogen co-doped carbon material capable of degrading organic dyes. The pyrolysis raw material used is a mixture of a homemade iron-containing solid powder and a triazole nitrogen source. Chinese patent CN115583647B discloses a method for preparing an oxygen-, nitrogen-, and metal-codoped carbon material for rubber reinforcement. The raw materials used are a mixture of polysuccinimide, ethylenediamine, and the metal salts Cd(NO3)3·4H2O and Na2SnO3·3H2O. Summary of the Invention

[0005] The purpose of the present invention is to address the deficiencies in the preparation process and catalytic performance of carbon nanomaterials, provide a highly dispersed iron, nitrogen, oxygen and other multi-component co-doped carbon nanobelts and their preparation method, and promote the application of persulfate-based advanced oxidation technology in the treatment of organic wastewater.

[0006] The technical solution of the present invention is: a method for preparing highly dispersed multi-component co-doped carbon nanobelts, characterized by comprising the following steps:

[0007] (1) Add aniline monomer and inorganic iron source in an acidic environment, wherein the inorganic iron source is a soluble iron salt or basalt fiber, and stir evenly;

[0008] (2) adding an oxidant solution dropwise, stirring the reaction to carry out oxidative polymerization, separating a dark green solid product after the reaction is completed, washing and drying it, and obtaining an iron-modified partially oxidized polyaniline precursor;

[0009] (3) The precursor obtained in step (2) is subjected to high-temperature carbonization under the protection of an inert atmosphere to obtain highly dispersed multi-component in-situ co-doped carbon nanobelts.

[0010] In the technical solution of the present invention, an iron-modified partially oxidized polyaniline precursor is prepared through a Fenton-like oxidation process in an acidic environment. The Fenton-like reaction system consists of an inorganic iron source and an oxidant. When persulfate is used as the oxidant, four doping elements (iron, nitrogen, oxygen, and sulfur) are introduced into the final carbon material.

[0011] Preferably, in step (1), the acidic environment is one of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 0.5 to 5 M, the soluble iron salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate, and the mass content of Fe in the basalt fiber is 3% to 5%. The optimal concentration of the acidic environment is 1 M.

[0012] Preferably, in step (1), the volume of the acidic environment is 5 to 50 times the volume of aniline. More preferably, the volume of the acidic environment is 30 times the volume of aniline.

[0013] The basalt fibers used in the present invention are commercially available chopped fibers with a length specification of 3 to 100 mm. In step (2), when the inorganic iron source is basalt fibers, after the reaction is completed, the residual basalt fibers are first removed, and then centrifuged to separate the dark green solid product. When the inorganic iron source is a soluble iron salt, the dark green solid product is directly centrifuged after the reaction is completed.

[0014] Preferably, in step (2), the stirring speed is 300-750 rpm, and the stirring time is 1-5 h.

[0015] Preferably, in step (2), the oxidant comprises one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and potassium persulfate, and the mass concentration of the oxidant solution is 1 to 30%. The oxidant solution (solvent is water) is added dropwise or using a peristaltic pump, preferably within 5 to 30 minutes.

[0016] Preferably, the molar ratio of the aniline, oxidant and inorganic iron source is 1:(0.4-5):(0.0013-0.5), and the optimal ratio is 1:0.9:0.25. The polymerization temperature in step (2) is 0-50°C, and the optimal temperature is room temperature.

[0017] Preferably, in step (3), the inert atmosphere protection is one of nitrogen, helium, and argon, and the heating rate is 5 to 30°C / min.

[0018] Preferably, the carbonization temperature is 700-900° C., and the carbonization time is 1-3 hours.

[0019] The present invention also provides a highly dispersed multi-component co-doped carbon nanobelt, which is prepared according to any of the above methods for preparing highly dispersed multi-component co-doped carbon nanobelts.

[0020] The present invention also provides a method for treating organic wastewater using highly dispersed multi-component co-doped carbon nanobelts. The material can be used to activate monopersulfate to selectively generate singlet oxygen, effectively degrading organic pollutants such as dyes and drug molecules in water.

[0021] Preferably, highly dispersed multi-component co-doped carbon nanobelts and monopersulfate are added to organic wastewater and stirred for reaction to degrade pollutants in the organic wastewater. The pollutants in the organic wastewater include one or more of drug molecules and dyes. The pH of the organic wastewater is 5-9, and the pollutant content in the organic wastewater is 0.1-50 mg / L. The amount of highly dispersed multi-component co-doped carbon nanobelts added is 0.2-1 g per liter of organic wastewater, and the amount of monopersulfate added is 0.1-0.6 g per liter of organic wastewater. The monopersulfate is generally potassium monopersulfate.

[0022] Among the pollutants, the dye includes one or more of Congo red, rhodamine B, and orange G. The drug molecules include one or more of sulfamethoxazole and acetaminophen.

[0023] The beneficial effects of the present invention include:

[0024] 1. In the preparation method of the present invention, aniline is used as the starting carbon source and nitrogen source, and inorganic iron and peroxide in a Fenton-like reaction system are used as the iron source and oxygen source respectively (when persulfate is used as an oxidant, persulfate can also be used as a sulfur source), and an iron-modified partially oxidized polyaniline precursor is prepared by a Fenton-like oxidation method. The strongly acidic environment of the polymerization reaction system can promote the dissolution, polymerization and doping of aniline, which is conducive to using natural iron-containing ores such as basalt as an iron source to reduce costs. It can also avoid the precipitation reaction of iron ions, remove the weakly adsorbed iron species on the polyaniline polymer chain, and provide a suitable single precursor for the subsequent high-temperature carbonization to directly prepare highly dispersed iron, nitrogen and oxygen multi-component in-situ co-doped carbon nanobelts. The carbonization process does not require an external carbon source and other doping raw materials, nor does it require a subsequent pickling step, and can prepare atomic-level highly dispersed iron, nitrogen and oxygen multi-component in-situ co-doped carbon nanobelts in one step.

[0025] 2. The present invention creatively combines modification technologies such as morphology control, element doping and defect engineering. By adjusting the microstructure, elemental composition and defect sites of the carbon material, a multi-component co-doped carbon nanobelt such as iron, nitrogen and oxygen is designed and prepared. Through the synergistic effect between multiple active sites, monopersulfate is activated to selectively generate singlet oxygen, effectively degrading various organic pollutants in complex water bodies.

[0026] 3. The co-doped carbon nanobelts produced by the present invention, activated with potassium monopersulfate, exhibited excellent degradation effects on Congo red, rhodamine B, Orange G, sulfamethoxazole, and acetaminophen, achieving degradation rates of 88.4%, 99.2%, 99.9%, 83.8%, and 99.7% after 60 minutes, respectively. Furthermore, the co-doped carbon nanobelts produced by the present invention exhibited excellent recyclability and could be directly recycled without post-treatment, maintaining a high activity of 98.8% after four consecutive uses. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 TEM image of highly dispersed multi-component co-doped carbon nanobelts prepared in Example 1;

[0028] Figure 2 This is the full XPS spectrum of the highly dispersed multi-component co-doped carbon nanoribbons prepared in Example 1;

[0029] Figure 3 This is the pore size distribution diagram of the highly dispersed multi-component co-doped carbon nanobelts prepared in Example 1;

[0030] Figure 4 This is a diagram showing the effect of highly dispersed multi-component co-doped carbon nanobelts on degrading organic pollutants in Example 1;

[0031] Figure 5 This is a graph showing the recycling performance of the highly dispersed multi-component co-doped carbon nanobelts in Example 1. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0033] Example 1

[0034] This embodiment provides a method for preparing highly dispersed multi-component co-doped carbon nanoribbons, the steps of which are as follows:

[0035] (1) Add 0.7592 g of FeCl3·6H2O and 1 mL of aniline to 30 mL of HCl (1 M concentration, i.e., 1 mol / L) solution and stir well.

[0036] (2) 6.0 mL of a 5.5% H₂O₂ aqueous solution was added dropwise over 8 minutes. In this example, the molar ratio of aniline, oxidant, and inorganic iron salt was 1:0.9:0.25. The reaction was incubated at 25°C and 600 rpm for 3 hours. The reaction mixture was centrifuged to recover a dark green solid. The solid product was washed with deionized water and ethanol, respectively, and then transferred to a watch glass and dried overnight at room temperature to obtain the precursor.

[0037] (3) The precursor obtained in step (2) was placed in a 20 mL quartz tube, and in a tube furnace under a N2 atmosphere, the temperature was raised from 30 ° C to 800 ° C at a rate of 5 ° C / min and maintained for 1 hour to achieve high-temperature carbonization. After slowly cooling to room temperature, a black solid was obtained, i.e., a highly dispersed multi-component co-doped carbon nanobelt.

[0038] Figure 1 The results showed that the black solid powder had a one-dimensional ribbon-like graphite phase microstructure and no iron-containing nanoparticles were observed, proving that the doped iron element was highly dispersed. Figure 2 It can be seen that the black solid powder contains three elements: carbon, nitrogen and oxygen. The iron content measured by ICP-OES is 0.47%. Figure 3 It can be seen that the black solid powder has a multi-level pore structure.

[0039] Example 2

[0040] This embodiment provides a method for preparing highly dispersed multi-component co-doped carbon nanoribbons, the steps of which are as follows:

[0041] (1) Add 0.0379 g FeCl3·6H2O and 1 mL aniline to 30 mL HCl (1 M) solution and stir well.

[0042] (2) 6.0 mL of a 5.5% H₂O₂ aqueous solution was added dropwise over 8 minutes. In this example, the molar ratio of aniline, oxidant, and inorganic iron salt was 1:0.9:0.0125. The reaction was carried out at 25°C and 600 rpm for 3 hours. The reaction mixture was centrifuged to recover a dark green solid. The solid product was washed with deionized water and ethanol, respectively, and then transferred to a watch glass and dried overnight at room temperature to obtain the precursor.

[0043] (3) The precursor obtained in step (2) was placed in a 20 mL quartz tube, and the temperature was raised from 30 ° C to 900 ° C at 5 ° C / min in a tube furnace under N2 atmosphere, and then maintained for 1 hour to achieve high-temperature carbonization. After slowly cooling to room temperature, a black solid was obtained, i.e., highly dispersed multi-component co-doped carbon nanobelts.

[0044] Example 3

[0045] This embodiment provides a method for preparing highly dispersed multi-component co-doped carbon nanoribbons, the steps of which are as follows:

[0046] (1) Add 1.1290 g FeCl3·6H2O and 1 mL aniline to 30 mL HCl (1 M) solution and stir well.

[0047] (2) 6.0 mL of a 5.5% H₂O₂ aqueous solution was added dropwise over 8 minutes. In this example, the molar ratio of aniline, oxidant, and inorganic iron salt was 1:0.9:0.38. The reaction was incubated at 25°C and 600 rpm for 3 hours. The reaction mixture was centrifuged to recover a dark green solid. The solid product was washed with deionized water and ethanol, respectively, and then transferred to a watch glass and dried overnight at room temperature to obtain the precursor.

[0048] (3) The precursor obtained in step (2) was placed in a 20 mL quartz tube, and the temperature was raised from 30 ° C to 900 ° C at 5 ° C / min in a tube furnace under N2 atmosphere, and then maintained for 1 hour to achieve high-temperature carbonization. After slowly cooling to room temperature, a black solid was obtained, i.e., highly dispersed multi-component co-doped carbon nanobelts.

[0049] Example 4

[0050] This embodiment provides a method for preparing highly dispersed multi-component co-doped carbon nanoribbons, the steps of which are as follows:

[0051] (1) Add 0.5023 g of basalt fiber (iron content: 3.28%, specification is 6 mm long short-cut fiber) to 30 mL of HCl (1 M) solution and stir for 10 min. Then add 1 mL of aniline and stir evenly.

[0052] (2) 6.0 mL of a 5.5% H₂O₂ aqueous solution was added dropwise over 6 minutes. In this example, the molar ratio of aniline, oxidant, and iron contained in the basalt fiber was 1:0.9:0.027. The reaction was continued at 25°C and 600 rpm for 3 hours. The basalt fiber was removed and the reaction mixture was centrifuged to recover dark green solid particles. The solid product was washed with deionized water and ethanol, respectively, and then transferred to a watch glass and dried overnight at room temperature to obtain a precursor.

[0053] (3) The precursor obtained in step (2) was placed in a 20 mL quartz tube, and in a tube furnace under a N2 atmosphere, the temperature was raised from 30 ° C to 800 ° C at a rate of 5 ° C / min and maintained for 1 hour to achieve high-temperature carbonization. After slowly cooling to room temperature, a black solid was obtained, i.e., a highly dispersed multi-component co-doped carbon nanobelt.

[0054] Examples 5-9

[0055] The highly dispersed multi-component co-doped carbon nanobelts prepared in Example 1 were used to activate potassium monopersulfate to degrade organic pollutants. The specific steps are as follows:

[0056] In a 60 mL two-necked flask, 0.025 g of the catalyst prepared in Example 1 and 50 mL of an aqueous solution containing 25 mg / L of organic pollutants (including Congo red, rhodamine B, orange G, sulfamethoxazole and acetaminophen, corresponding to Examples 5-9, respectively) were added in sequence. After stirring and pre-adsorption for 30 min at 25 ° C and 600 rpm, 0.015 g of potassium monopersulfate was added to start the reaction. The residual concentration C of the organic matter was measured at regular intervals. t , with the residual concentration C t / Original concentration C s The corresponding degradation kinetic curve was drawn based on the ratio.

[0057] Depend on Figure 4 The catalyst-activated potassium monopersulfate exhibits excellent degradation effects on common organic pollutants, including pharmaceutical molecules and dyes. Congo red, rhodamine B, orange G, sulfamethoxazole, and acetaminophen were degraded by 88.4%, 99.2%, 99.9%, 83.8%, and 99.7% of the respective degradation rates within 60 minutes. Specific degradation data are shown in Table 1.

[0058] Table 1 Catalyst activation of potassium monopersulfate for pollutant degradation

[0059]

[0060] Example 10

[0061] Recycling performance of the highly dispersed multi-component co-doped carbon nanobelts prepared in Example 1:

[0062] In a 60 mL two-necked flask, 0.025 g of the above catalyst and 50 mL of a 25 mg / L acetaminophen aqueous solution (pH 6.90) were added sequentially. Pre-adsorption was carried out at 25°C and 600 rpm for 30 minutes. Then, 0.015 g of potassium monopersulfate was added. The acetaminophen concentration in the residual solution was measured at regular intervals, and a corresponding degradation kinetic curve was plotted. After a 60-minute reaction, the catalyst was recovered by centrifugation. Following the aforementioned procedure, 50 mL of a 25 mg / L acetaminophen aqueous solution and 0.015 g of potassium monopersulfate were added to begin a second performance test, and so on.

[0063] Depend on Figure 5 The catalyst exhibits excellent recyclability and can be directly recycled without post-treatment, maintaining high activity after four consecutive uses. The degradation rates for the first, second, third, and fourth cycles reached 99.7%, 99.9%, 99.7%, and 98.8% for 60 minutes, respectively. Specific degradation data are shown in Table 2 below.

[0064] Table 2 Catalyst recycling and activation of potassium monopersulfate for degradation of acetaminophen

[0065]

[0066] The above embodiments are merely examples for the purpose of clearly illustrating the present invention and are not intended to limit the embodiments. Those skilled in the art will appreciate that other variations or modifications may be made based on the above descriptions. It is not necessary and impossible to enumerate all embodiments here. Therefore, any obvious variations or modifications derived therefrom remain within the scope of protection of the present invention.

Claims

1. Application of highly dispersed multi-component co-doped carbon nanobelts in organic wastewater treatment, characterized in that: The method for preparing highly dispersed multi-component co-doped carbon nanobelts comprises the following steps: (1) Add aniline monomer and inorganic iron source in an acidic environment, the inorganic iron source is soluble iron salt or basalt fiber, and stir evenly; (2) adding an oxidant solution dropwise, stirring the reaction to carry out oxidative polymerization, separating a dark green solid product after the reaction is completed, washing and drying the product, and obtaining an iron-modified partially oxidized polyaniline precursor; (3) The precursor obtained in step (2) is subjected to high-temperature carbonization under the protection of an inert atmosphere to obtain highly dispersed multi-component in-situ co-doped carbon nanobelts.

2. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: In step (1), the acidic environment is one of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 0.5-5M, the soluble iron salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate, and the mass content of Fe in the basalt fiber is 3%-5%.

3. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: In step (2), the stirring speed is 300-750 rpm, and the stirring time is 1-5 h.

4. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: In step (2), the oxidant includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and potassium persulfate.

5. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: The molar ratio of the aniline, the oxidant and the Fe contained in the inorganic iron source is 1:(0.4-5):(0.0013-0.5).

6. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: In step (3), the inert atmosphere protection is one of nitrogen, helium and argon, and the heating rate is 5 to 30°C / min.

7. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: In step (3), the carbonization temperature is 700-900° C., and the carbonization time is 1-3 hours.

8. The use of the highly dispersed multi-component co-doped carbon nanobelt in organic wastewater treatment as claimed in claim 1, characterized in that: Specifically include: Highly dispersed multi-component co-doped carbon nanobelts and monopersulfate are added into organic wastewater for reaction by stirring, so as to degrade pollutants in the organic wastewater, wherein the pollutants in the organic wastewater include one or more of drug molecules and dyes, the pH of the organic wastewater is 5-9, the content of pollutants is 0.1-50 mg / L, the amount of highly dispersed multi-component co-doped carbon nanobelts is 0.2-1 g per liter of organic wastewater, and the amount of monopersulfate is 0.1-0.6 g per liter of organic wastewater.

Citation Information

Patent Citations

  • A nitrogen-doped carbon nanosheet, its preparation method and its application

    CN111744523B

  • Preparation methods of oxygen, nitrogen and metal co-doped carbon materials and their applications in rubber

    CN115583647B

  • Nitrogen-doped carbon material, preparation method and application thereof, adsorption material and application thereof

    CN116550285A

  • Iron and nitrogen co-doped carbon material as well as preparation method and application thereof

    CN117138815A

  • Doped polyaniline directly-carbonized composite electrocatalyst, preparation method and application

    CN103007976A